Isolation and Screening of the Enzymatic Potential of Lactic Acid Bacteria from VCO Oil Cake - Putri, Riski Dwimalida; Balkis, Atia (Jurnal Kimia Riset, 2025)
Virgin coconut oil (VCO) has various health benefits. In the VCO production process using fermentation, a by-product is produced as a solid called oil cake. In this study, lactic acid bacteria were isolated from oil cake VCO, characterized and tested for antimicrobial activity against E. coli and S. aureus bacteria. Screening of enzymatic activity was also carried out as amylolytic, proteolytic, and lipolytic activities. From the study, four isolates were obtained, namely BL1, BL2, BL3, and BL4. The isolates have the characteristics of lactic acid bacteria in the form of circular colonies, white and milky white, gram-positive and do not have catalase activity. Based on observations, it is suspected that the bacterial isolates belong to the Lactobacillaceae and Streptococcaceae families. Four isolates have moderate antibacterial activity against S. aureus. The largest inhibition zone owned by isolate BL1 about 9.5 mm in diameters. Four isolates have antibacterial activity against E. coli with a weak category. The enzymatic potential test shows that isolate BL 1 has amylase and protease enzyme activity, while isolates BL2 and BL3 only have amylase enzyme activity.